Analisis Potensi Bahaya dan Upaya Pengendalian Risiko Bahaya Pada Pekerja Pemecah Batu - Setyaningsih, Yuliani; Wahyuni, Ida; Jayanti, Siswi (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2010)
Risk Assessment is an activity that analyze a risk by determining the likelihood/ probability and severity ofconsequence / Consequences of a risk. This study is aimed to describe and assess the risk level in terms ofworker characteristics, equipment, materials, work processes and working environment of stone breakersworkers and making recommendations on hazard control efforts of workers.This was a descriptive qualitative research by conducting interviews on the workers and make observations onthe environment and work processes, and measuring the work environment. The study population was allworkers in the village of stone breaker Rowosari, Tembalang, Semarang with a sample of 41 people taken bysimple random sampling. Qualitative data analysis with content analysis using the form Hazard Identificationand Risk Assessment (HIRA).Results from this study is the level of risk of accidents at stone-breaking workers of each variable: thecharacteristics of workers with medium category, such as basket work tools, hammers, ganco and chairs with themedium category, with categories of stone material from the medium, such as the work process collecting,splitting, collecting and collating the stone with the medium category, and work environment with the mediumcategory. Workers are expected to wear the working tools such as carts and wearing personal protectiveequipment such as masks and gloves in order to reduce the risk of hazards during work.Keywords: risk assessment , stone breaking employees. Hazard Identification and Risk Assessment (HIRA)http://ejournal.undip.ac.id/index.php/mkmi/article/view/2906Â